Pediatric Pleural Effusion and Pneumococcal Vaccination Trends in the Pre- and Post-COVID Era: A Single-Centre Retrospective Study - Denisa Lavinia Atanasiu; Maria Mitrica; Luciana Petrescu; Oana Falup-Pecurariu; Laura Bleotu; Raluca Ileana Lixandru; David Greenberg; Alexandra Grecu (Children)
Background/Objectives: Pleural effusion represents an accumulation of fluid in the pleural cavity, frequently associated with pneumonia. There has been a gradual increase in cases among children in recent years, with a notable rise during the post-pandemic period, potentially due to immune debt, decreased vaccination coverage, and changes in pathogen dynamics. Methods: We enrolled 66 children with pleural effusion treated at the Children’s Emergency Clinical Hospital, Brasov, between January 2019 and September 2024. We analyzed the data on demographics, symptoms, vaccination status, hospitalization, and treatments to assess the trends in the incidence and clinical features. Results: The median age was 5 years (ranging from 3 months to 17 years). Most patients were male (57.5%) from rural areas (34.8%). Only 40.9% fulfilled the vaccination schedule of Romania. We observed a rise in hospitalizations in the last two years, with 16 cases in 2023 and 15 in 2024, and most were being admitted in April (15.5%). Patients mainly had severe (36%) and medium (26%) acute respiratory failure. S. pneumoniae was the most common isolate with two cases each of serotype 1, 14, and 23A, and one case each of serotype 3, 31, and 34, followed by H. influenzae and P. aeruginosa. Treatment was mostly with ceftriaxone (69.6%), Vancomycin (63.6%), Meropenem (53.0%), and Teicoplanin (25.7%). Some children required thoracic drainage (34.8%). Complications like pneumothorax (16.6%), polyserositis (4.5%), and pneumomediastinum (3.0%) were found. Conclusions: The rise in pleural effusion cases may be influenced by various factors, such as changes in pathogen behavior or host immune responses following the pandemic. Further research is needed to understand these potential mechanisms. The emergence of non-PCV20 strains and the common occurrence of serotype 3 infections point out the need to study serotype trends and evaluate whether expanding vaccine programs could be beneficial.